P232 IQCARO project: A decalogue to improve quality of care through patient′s eyes. (16th January 2018) - Calvet, X; Carpio, D; Minguez, M; Vera, I; Marin, L; Saldaña, R; Juliá, B; Cea-Calvo, L; Casellas, F
Abstract: Background: It is becoming increasingly necessary to measure the quality of care(QoC) that we provide to our patients with IBD. Patient's perspective should be taken into account for all aspects of care. The aim of the IQCARO project was to select a decalogue of quality indicators of the IBD units, that were selected and could be reliably evaluated from a patients′ perspective Methods: After an extensive literature search, an expert panel composed of specialists in IBD, nurses and patients selected 54 indicators. These indicators were presented to 16 patients in two focus groups who analysed the quality indicators for understandability and reliability. Participant patients were selected from the Spanish associations of patients with IBD, and from different IBD units. Subsequently a Delphi consensus-based approach with a web-based two voting rounds was used for IBD patients to select a final set of ten quality of care (QoC) indicators. Patients assessed the importance of each indicator using a Likert scale from 1 (not important) to 9 (very important). After the second round, patients were asked to choose the "top ten indicators" and place them in order according to their importance. To decide the final list of indicators and to avoid tie, an utility ratio was calculated for each item with the formula: % of participants that voted the indicator (%P) as the most important (MI) x10 + (%P) as the second MI x9… until +(%P) as the less MI x1. Results: Twenty-six patients participated in two rounds Delphi consensus (54% males, 54%CD). The selection of the "top ten" indicators according to their importance covered the care dimensions of: Structure (5 indicators); Process (4 indicators); and outcome (1 indicator). Conclusions: The present Delphi consensus identified a QoC Decalogue that were developed exclusively from patient′s perspective. This evaluation fully independent of health care staff may be useful for developing improvement strategies for IBD patients management This Project was funded by Merck Sharp and Dohme of Spain and endorsed by ACCU and GETECCU